They're Here! How to Prepare Your Blood Bank for Inspection. Issue 1 (29th August 2015) - Byrne, Karen M.; Frank, Ernest G.; Gedman, Lauren A.; Ivey, Julie R.
Abstract : The importance of an inspection ready blood bank cannot be overemphasized. Various agencies perform inspections to ensure that facilities are compliant with federal and state regulations, as well as with standards defined by professional organizations. Inspections may strike fear into the staff members of the organizations being inspected. When a laboratory is in a state of constant readiness, such anxiety is likely to be lessened. Facilities may differ in structure and size and yet be held to the same standards. This article discusses the who, when, and why of laboratory safety inspections. We share helpful information gathered from various resources, including interviews with a quality assurance specialist, a blood bank manager, and an assessor, to help facilities work towards an inspection ready state.